The History of Conflict and Human Rights in East Timor : Peace and Human Rights - dos Santos, Hercus Pereira (Yayasan Meira Visi Persada, 2025)
The history of the United Nations began after the Second World War with the main objective of preserving peace and international security and avoiding wars in the world. This objective was set precisely because of the experience of the first and second world wars that caused the damage and strong catastrophe for human life and the world. From the birth of the United Nations, it is possible to see that many nations benefit from the support of the United Nations to solve their problems, especially the problem of the right of self-determination and the independence of the country in the regions of Asia and Africa and in the name of Human Rights, the United Nations can interfere and sanction nations that endanger Human Rights, that is, Human Rights issues are no longer considered only as an internal problem of the country but it becomes like a problem in which the United Nations has the legitimacy and authority to interfere. Over time, many movements for solidarity and the defense of Human Rights were born. During the time of the struggle for Independence, Timor-Leste also benefited from the support of the United Nations in which at the very first moment of the invasion of Indonesia, the United Nations Security Council issued a resolution to contest the invasion of Indonesia and the United Nations decided not to recognize the proclamation of the Independence of Timor-Leste on November 28, 1975 made by the Revolutionary Front Timor-Leste Independent and at the same time also did not recognize the integration of Balibo made by Apodeti and UDT and with support from Indonesia. The United Nations held the referendum in Timor-Leste on 30 August 1999 and then also helped to prepare a new state of Timor-Leste under the United Nations Transitional Administration in East Timor and recognised the Independence of Timor-Leste on 20 May 2002. After the 20th of May 2002, the United Nations continues to support Timor-Leste until now. It can be seen that the role of the United Nations in the construction of the state of Timor-Leste is very important in the preparation of the Constitution of Timor-Leste, in the reconciliation of the CAVR (Reception, Truth and Reconciliation Commission), in the training of the National Police of Timor-Leste and the Armed Forces of Timor-Leste, in the resolution of existing conflicts within Timorese society and through direct intervention or through training and advice in the institutions of the state of Timor-Leste.